Tabungan Pintar Berbasis Single Board Computer - Kevin Rahmat Trisnoyo; Rian Ferdian (CHIPSET, 2020)
At this time the piggy bank or savings began to be abandoned because many people save money in the bank. but if it is intended to save daily then it is not effective to choose a bank. this makes people no longer cultivate daily savings which is very good to save daily. the problem is also because generally the container for daily savings called piggy bank is generally small in size and easy to open or mostly just destroyed. then we need a piggy bank that is practical and sophisticated and also not easy to take so it helps to keep the saver from controlling his patience in saving. In order to create a sophisticated savings box, an embedded system is implemented that can make savings plans with a nominal money detection feature using the object detection method so that later savings can calculate the amount of money saved and savers can see it. YOLO is one object detection method that can be applied. Before that savers can make a saving plan by including the maximum target of saving desired and the old target of saving needed so that savers can be more structured in saving because they have clear objectives in their planning.